STRATEGI PENGUATAN PEREKONOMIAN INDONESIA DI MASA PANDEMI COVID-19 MELALUI PEMUTAKHIRAN KEBIJAKAN SUBSIDI EKSPOR (Lex Jurnalica, 2022)
AbstractOne of the impacts of the Covid-19 pandemic is the impact on the international trade sector, including the export of primary and non-primary goods. Based on WTO rules, the provision of subsidies to non-primary products is prohibited, especially for developed countries, while many Indonesian non-primary products have supported the Indonesian economy and are currently experiencing quite a number of obstacles. This research is a juridical normative research. The main research questions of this research are: (1) How is the implementation of export subsidy policy for Indonesia; and (2) What is the strategy for strengthening the Indonesian economy during the COVID-19 pandemic through Indonesia's export subsidy policy enhancement. According to the research results, it can be concluded that: (1) Indonesia signed the "Code in Subsidies and Countervailing Duties" in 1985 and Bilateral Agreement in 1991 with the United States which means that the validity period of subsidies for Indonesia has ended. In addition, Indonesia becomes a member of the G-20 and no longer included as one of developing countries in the WTO list by the United States (USA), in 2020. The change of Indonesia's status has an impact on the thresholds de minimis of subsidies on imported goods to the US. The consideration is that the Covid-19 pandemic has changed Indonesia's position from the upper middle income level to the lower middle income level country. Therefore, the government needs to consider about the export subsidy policy enhancement, that is still aligning it with international regulations, to strengthen the interests of the national economy; and (2) In order to enhance the export subsidy policy in Indonesia, during the Covid-19 Pandemic, the government has been undertaking the economic recovery policies through the fiscal and taxation side, as well as customs facilities. Another policy in enhancing the export subsidy policy can be implemented by providing proportional direct subsidies for business actors.Keywords: Export Subsidy Policy, Indonesian Economy, Covid-19 PandemicAbstrakDampak dari adanya Pandemi Covid-19 salah satunya adalah dampak di sektor perdagangan internasional, tidak terkecuali di sektor ekspor barang primer maupun non primer. Berdasarkan aturan WTO, pemberian subsidi terhadap produk non primer ini dilarang, khususnya bagi negara maju, sementara banyak produk non primer Indonesia telah mendukung perekonomian Indonesia dan saat ini mengalami cukup hambatan. Penelitian ini adalah penelitian normatif yuridis. Rumusan masalah dalam penelitian ini adalah (1) Bagaimana penerapan kebijakan subsidi ekspor bagi Indonesia; dan (2) Bagaimana strategi penguatan perekonomian Indonesia di masa Pandemi Covid-19 melalui pemutakhiran kebijakan subsidi ekspor Indonesia. Dari hasil penelitian disimpulkan: (1) Indonesia tahun 1985 telah menandatangani “Code in Subsidies and Countervailing Duties” dan Perjanjian Bilateral dengan Amerika Serikat tahun 1991 yang menandakan mengakhiri masa berlakunya subsidi bagi Indonesia. Selain itu, ditandai pula dengan masuknya Indonesia ke dalam anggota G-20 serta dihapusnya Indonesia dari daftar negara berkembang di WTO oleh Amerika Serikat (AS) pada tahun 2020. Perubahan status Indonesia tersebut memberikan dampak pada tresholds de minimis subsidi atas barang impornya ke AS. Hal yang menjadi pertimbangan bahwa kondisi Pandemi Covid-19 telah mengubah posisi Indonesia dari level pendapatan menengah ke atas menjadi pendapatan menengah ke bawah. Pemerintah perlu mempertimbangkan pemutakhiran kebijakan subsidi ekspor untuk memperkuat kepentingan ekonomi nasional, dengan tetap menyelaraskan terhadap peraturan internasional; dan (2) Dalam rangka pemutakhiran kebijakan subsidi ekspor di Indonesia, pada masa Pandemi Covid-19, pemerintah mengupayakan kebijakan pemulihan ekonomi melalui sisi fiskal dan perpajakan, serta fasilitas kepabeanan. Kebijakan lain dalam pemutakhiran kebijakan subsidi ekspor dapat dengan pemberian subsidi langsung secara proposional bagi pelaku usaha.Kata Kunci: Kebijakan Subsidi Ekspor, Perekonomian Indonesia, Pandemi Covid-19